Post-insemination sexual selection in birds. - Pizzari, T (2007)
In many avian species females obtain sperm from multiple males during a single reproductive event, setting the scene for post-insemination sexual selection through the competition of the ejaculates of different males over fertilisation (sperm competition) and female biased utilisation of sperm (cryptic female choice). The use of poultry techniques in combination with molecular tools is catalysing an interest in birds as vertebrate model systems to study the mechanisms of post-insemination sexual selection. This chapter: (i) outlines the main mechanisms of avian sperm competition, (ii) introduces methodological approaches to study post-insemination sexual selection in birds, (iii) reviews recent evidence of multiple mechanisms of strategic sperm allocation by males, and (iv) discusses mechanisms of cryptic female choice. Post-insemination variance in paternity in birds, appears to be determined by the interactions between complex male and female strategies of differential sperm utilisation. It is argued that a better understanding of the operation of post-insemination sexual selection in birds may be achieved through a two-pronged approach which, on the one hand, investigates behavioural and physiological mechanisms applying poultry techniques and molecular tools to domestic model species, and on the other, verifies these mechanisms and tests their adaptive significance in more natural populations.